Silencing of lncRNA PKIA-AS1 Attenuates Spinal Nerve Ligation-Induced Neuropathic Pain Through Epigenetic Downregulation of CDK6 Expression - Hu, Jian-Zhong; Rong, Zi-Jie; Li, Miao; Li, Ping; Jiang, Li-Yuan; Luo, Zi-Xiang; Duan, Chun-Yue; Cao, Yong; Lu, Hong-Bin (Frontiers in Cellular Neuroscience, 2019)
Neuropathic pain (NP) is one of the intractable comorbidities of spinal cord injury. Emergence of long non-coding RNAs (lncRNAs) reveal key insights into transcriptional and translational mechanisms in chronic pain states. Here, we identified a novel lncRNA PKIA-AS1 by using lncRNA array in spinal cord tissues of spinal nerve ligation (SNL) model, and further investigated the role of PKIA-AS1 in neuropathic pain development. We observed that PKIA-AS1 was significantly increased in SNL rat models. Knockdown of PKIA-AS1 can attenuate neuropathic pain progression in SNL rats, and overexpression of PKIA-AS1 sufficient to mediate neuropathic pain symptoms. PKIA-AS1 mediates SNL-induced neuropathic pain by epigenetically regulating the expression and function of the CDK6, which is essential to the initiation and maintenance of neuroinflammation and neuropathic pain. In conclusion, PKIA-AS1 plays an important role in the pathogenesis of neuropathic pain through direct interaction CDK6. PKIA-AS1 silencing might be a complementary approach to reduce neuropathic pain induced by spinal nerve ligation through downregulation of CDK6 expression and function in mammals.